Mindfulness-based interventions for mental well-being among people with multiple sclerosis: a systematic review and meta-analysis of randomised controlled trials. Issue 9 (13th June 2019) - Simpson, Robert; Simpson, Sharon; Ramparsad, Nitish; Lawrence, Margaret; Booth, Jo; Mercer, Stewart W
Abstract : Objective: Impairment of mental well-being (anxiety, depression, stress) is common among people with multiple sclerosis (PwMS). Treatment options are limited, particularly for anxiety. The aim of this study was to update our previous systematic review (2014) and evaluate via meta-analysis the efficacy of mindfulness-based interventions (MBIs) for improving mental well-being in PwMS. Methods: Systematic searches for eligible randomised controlled trials (RCTs) were carried out in seven major databases (November 2017, July 2018), using medical subject headings and key words. Studies were screened, data extracted, quality appraised and analysed by two independent reviewers, using predefined criteria. Study quality was assessed using the Cochrane Collaboration risk of bias tool. Mental well-being was the primary outcome. Random effects model meta-analysis was performed, with effect size reported as standardised mean difference (SMD). Results: Twelve RCTs including 744 PwMS were eligible for inclusion in the systematic review, eight had data extractable for meta-analysis; n=635. Ethnicity, socioeconomic status, comorbidity and disability were inconsistently reported. MBIs varied from manualised to tailored versions, lasting 6–9 weeks, delivered individually and via groups, both in person and online. Overall SMD for mental well-being (eight studies) was 0.40 (0.28–0.53), p<0.01, I 2 =28%; against active comparators only (three studies) SMD was 0.17 (0.01–0.32), p<0.05, I 2 =0%. Only three adverse events were reported. Conclusions: MBIs are effective at improving mental well-being in PwMS. More research is needed regarding optimal delivery method, cost-effectiveness and comparative-effectiveness. PROSPERO registration number: CRD42018093171.